2017
DOI: 10.1371/journal.pgen.1006592
|View full text |Cite
|
Sign up to set email alerts
|

β-Integrin de-phosphorylation by the Density-Enhanced Phosphatase DEP-1 attenuates EGFR signaling in C. elegans

Abstract: Density-Enhanced Phosphatase-1 (DEP-1) de-phosphorylates various growth factor receptors and adhesion proteins to regulate cell proliferation, adhesion and migration. Moreover, dep-1/scc1 mutations have been detected in various types of human cancers, indicating a broad tumor suppressor activity. During C. elegans development, DEP-1 mediates binary cell fate decisions by negatively regulating EGFR signaling. Using a substrate-trapping DEP-1 mutant in a proteomics approach, we have identified the C. elegans β-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Caenorhabitis elegans is a powerful model in which to examine BM biology. CRISPR-Cas9-mediated homologous recombination has facilitated the generation of endogenously tagged laminin, type IV collagen, nidogen, integrin, and dystroglycan genes with genetically encoded fluorophores (Jayadev et al, 2019;Matsuo et al, 2019;Naegeli et al, 2017;Walser et al, 2017). C. elegans is also small and translucent, which allows live imaging of BMs from the embryo through adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Caenorhabitis elegans is a powerful model in which to examine BM biology. CRISPR-Cas9-mediated homologous recombination has facilitated the generation of endogenously tagged laminin, type IV collagen, nidogen, integrin, and dystroglycan genes with genetically encoded fluorophores (Jayadev et al, 2019;Matsuo et al, 2019;Naegeli et al, 2017;Walser et al, 2017). C. elegans is also small and translucent, which allows live imaging of BMs from the embryo through adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of phosphatases may explain changes in cell surface abundance of other glycoproteins including cell adhesion molecules. For example, PTPRJ/Dep-1 and PTPRF have been shown to regulate integrin activation and recycling, respectively (52,53). Thus, a decrease in phosphatase activity could lead to altered surface residence of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in wild type animals, DEB-1 decorates the basal actin stress fibers, with some localization to cell junctions (Figure 5c We next asked if this redistribution of DEB-1/vinculin is accompanied by the redistribution of TLN-1/talin (Cram, Clark, & Schwarzbauer, 2003;Moulder, Huang, Waterston, & Barstead, 1996) and PAT-3/β-integrin (Gettner, Kenyon, & Reichardt, 1995). We knocked down fln-1 using RNAi in animals expressing endogenously tagged TLN-1 or PAT-3 (Walser, Umbricht, Fröhli, Nanni, & Hajnal, 2017), and stained for F-actin and nuclei using phalloidin and DAPI, respectively. (Figure 1b).…”
Section: The Linc Complex Is Required For the Perinuclear Localizatmentioning
confidence: 98%